The value of facade improvement towards building image - Mohammad Affendy, Omardin (Pejabat Naib Canselor, 2009)
Introduction. The importance of good looking image for building in the practice of building design. It also discusses the basic understandings of building image , the method of colour scheme. Facade means the face or front of a building, part of a building which faces the street; outward appearance; illusion, deceptive appearance.